Annual grand meeting alumni / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
Malaysia has a lot of highly potential Universities that offer beneficial programmes for the alums. Most universities invented programmes for their alums yo tighten the relationship between the university and the alums. Alumni general meeting is one of the programmes that quite active by the university. What are Alumni Grand Meetings? Alumni General Meeting is a mass meeting between the graduated alums of the university. The university uses its facility for this event to meet the alums. It can also be held outside the campus, such as in a ballroom and hotel hall.